Allegory, Style And Dialectical Criticism In Fredric Jameson - Lopes, Wibsson (Revista Criação & Crítica, 2023)
The article starts from a reading of two of Jameson's main theoretical works, the book Marxism And Form (1974) and the book Political Unconscious (1981) to try to comprehend what the author understands by dialectical criticism, linked to an idea of dialectical style or writing. The concepts of ideology and allegory are fundamental in this endeavor, as we intend to show through a presentation of the method constructed by Jameson in his work Political Unconscious and subsequently rethought and refined until his most current works. We also go through some readers and commentators of Jameson's work to enrich the view of this author who presents an example of criticism and interpretation inspired by Marxism and Hegelian dialectics.